FENOMENA PERKAWINAN ANAK: DINAMIKA HUKUM DAN PROBLEMATIKA PENEGAKAN HUKUM KELUARGA DI INDONESIA - Nazar, Haura Salsabiela El Sabrina; Shalihah, Fithriatus (LPPM, Universitas Muhammadiyah Riau, 2024)
In Indonesia, child marriage is still a complicated problem that hasn't been handled. A kid's well-being is harmed by the practice of child marriage, which violates children's human rights. Several initiatives have been undertaken, such as amending Law No. 16 of 2019 regulating Marriage to change the minimum age for marriage. This, however, is still unable to address Indonesia's issue of underage marriage. The Republic of Indonesia's Supreme Court's Directory of Decisions reveals a notable increase in requests for marriage dispensation following the adoption of new laws of the legal age of marriage. This research is normative legal research. This study aims to examine the legal dynamics and problems of family law enforcement in the practice of child marriage in Indonesia. Based on the findings, the government is trying to lower the emergency rate of child marriage in Indonesia by enacting laws that tighten marriage dispensation procedures and refresh the minimum age of marriage. In addition to the national strategy program for avoiding child marriage, efforts have been made to safeguard children's rights against the practice of underage marriage through the swift formation of rules in various areas. Despite recent legal updates to the marriage age, child marriage is still a common practice in Indonesia because family law is not strictly enforced in the country. Among the factors contributing to the law enforcement conundrum surrounding child marriage are the social realities of Indonesian society, the discordance of adult age limits, and the many interpretations of the word urgent reasons.